The law on sport in the light of the opinion of the fitness instructors and personal trainers - Proskura, Patrycja; Witkowski, Kazimierz (Quality in Sport, 2017)
Streszczenie Popularność pracy w charakterze instruktora fitness oraz trenera personalnego w naszym kraju stale rośnie. Prawo dotyczące tej grypy zawodowej w Polsce nie jest uregulowane, co stwarza wiele wątpliwości dotyczących jakości ich kwalifikacji. Obowiązująca ustawa o sporcie z dnia 25 czerwca 2010 roku m.in. zrównała wymogi dla trenerów i instruktorów, wykluczyła wymóg ukończenia studiów wyższych oraz wyłączyła procedurę ubiegania się o zgodę ministra właściwego do spraw kultury fizycznej na prowadzenie specjalistycznych kursów trenerskich i instruktorskich. Celem artykułu było zbadanie odczuć samych instruktorów fitness oraz trenerów personalnych dotyczących obecnej ustawy o sporcie. Badania przeprowadzono we wrocławskich klubach fitness, w których wzięło udział 100 ankietowanych. Abstract The popularity of the work as a fitness instructor and personal trainer in our country continues to grow. Right about this flu in Poland is not regulated, which creates a lot of concerns about the quality of their qualifications. The existing law on sport of 25 June 2010 requirements for trainers and instructors, excluded the requirement of graduate and cut off the procedure of applying for consent to the competent Minister of physical culture to carry out specialized trainer courses and instructor. The aim of the article was to examine the experience of the same fitness instructors and personal trainers on the current law on sport. The research was conducted in various fitness clubs, involving 100 respondents.